Fabrication of low-loss SOI nano-waveguides including BEOL processes for nonlinear applications - Tian H.; Winzer G.; Gajda A.; Petermann K.; Tillack B.; Zimmermann L. (Journal of the European Optical Society-Rapid Publications, 2012)
We report successful fabrication of low-loss SOI nano-waveguides with integrated PIN diode structures. The entire fabrication process is done on a 200 mm BiCMOS toolset using front-end-of-line (FEOL) and back-end-of-line (BEOL) processes and does not show any undesirable influence upon the photonic performance. Such a waveguide technology forms an attractive platform for a wide range of nonlinear applications due to efficient free carrier removal as well as use of standard substrates and processing technology. Nonlinear experiments were conducted to investigate the potential of the introduced technology. The performance of the designed waveguides can be used as a benchmark for future development of proposed platform for integrated silicon photonics and electronics circuits.